Studi Deskriptif: Analisis Tematik pada Nilai-nilai Adat dan Budaya dalam Sosialisasi Orang Tua yang Berasal dari Suku Minangkabau kepada Anak - Zahrahnabila, Zahrahnabila; Kania, Tarisa Putri (YASIN, 2024)
Value socialization is a process by which individuals learn the values, norms, and behaviors accepted in the society in which they live. The family as the child's first environment, plays an important role as a media channel in disseminating the values that exist in society to children this study uses a qualitative approach design conducted with the use of open ended questionnaire that is a questionnaire that can capture varied responses from various participants.Socialization of Indigenous values of Minangkabau culture is a very important process in maintaining and passing down cultural wealth from one generation to the next. Minangkabau people, which is a tribe that inhabits the territory of West Sumatra. As the largest matrilineal tribe in the world, the Minangkabau have a strong Indigenous value system that reflects their close relationship with nature, tradition, and local wisdom. The Minangkabau people pass on cultural heritage through the maternal line, and this socialization process generally occurs in families, communities, and indigenous institutions. Values such as adab, the value of mutual assistance, mutual respect, and active involvement in the lives of large families and communities become the main focus of the family has a central role in the socialization of the Indigenous values of Minangkabau culture. Researchers highlight the importance of the role of parents as value bearers and primary teachers in Minangkabau families, especially mothers. Mothers are not only responsible for educating children in terms of daily habits, but also for passing on cultural heritage through stories and practices that may be of a more traditional nature. Socialization of Indigenous values of Minangkabau culture is not limited to the family sphere, socialization of Indigenous values of Minangkabau culture is not only informational, but also involves direct experience that deepens understanding and appreciation of their cultural wealth.